THE THEORIES OF CONSUMER SOCIETY IN CONTEMPORARY PHILOSOPHY - E. A. Sergodeeva; E. Y. Mishchenko (Гуманитарные и юридические исследования)
The article is aimed at theoretical reconstruction of fundamental tenets of the theory of the consumer society in contemporary philosophy. The authors explore their social and cultural context, offer a classification and characterize conceptual apparatus. The author substantiates the thesis that pluralism of approaches to understanding of the consumer society is a theoretical and methodological framework for the development of alternative methods and philosophical approaches to the development of modern societies and resolve problems associated with the consumption.